Students’ perceptions on parental background and their academic performance in Islamic studies in Nigeria - Yunus, Aliyu; Mohd. Isa Hamzah; Khadijah Abdul Razak; Maimun Aqsha Lubis Abdin Lubis (Penerbit Universiti Kebangsaan Malaysia, 2018)
Parental background and academic performance have been a major research area carried out by numerous researchers. Many studies have focused on different variables that can encumber academic grades of students like Mathematics, English; among others. This current study investigates the perceptions of Islamic Studies’ students based on parental background such as education, occupation, income and involvement and their academic performance in Islamic Studies in north-central Nigeria. A sample of 384 students offering Islamic Studies in secondary school in the country served as respondents for this study. The data collected were analysed using SPSS version 23.0. Based on statistical finding on dimension of parental background that influences students’ academic performance in Islamic Studies; the majority of the students strongly perceived that, their parental background such as education with a mean of 3.47, occupation with a mean of 2.85, income with a mean of 2.68 and involvement with a mean of 3.47 greatly influenced their academic performance in Islamic Studies in north-central Nigeria. In conclusion, school management, teachers and parents should collaborate in enhancing students’ academic performance in Islamic Studies in various public secondary schools in north central in particular and the country in general.